Penilaian Interpersonal Mahasiswa Bimbingan Penyuluhan Islam dalam Konflik Komunikasi Interpersonal: Faktor Penyebab dan Strategi Penyelesaian Konflik - Guru Singa, Maratus Soleha; Sihombing, Nur Asia; Nsr, Nurraudhoh Rani; Mardiyah, Ainul (IAINU Kebumen, 2025)
Interpersonal communication conflict is a common issue in academic environments, including among students of Islamic Guidance and Counseling (Bimbingan Penyuluhan Islam/BPI). This study aims to identify the factors causing interpersonal communication conflicts, evaluate students’ interpersonal judgment abilities, and describe the conflict resolution strategies used. A qualitative approach was employed, using interviews with five BPI student respondents. The findings reveal that the primary causes of conflict include differences in communication styles, lack of openness, high ego, low empathy, and poor emotional control. Students’ interpersonal judgment abilities were found to vary and were not uniformly developed. The conflict resolution strategies applied tended to be empathetic, reflective, and prioritized personal communication. These findings recommend the importance of developing practical and consistent interpersonal communication skills among students.